The discriminant of an equation in the form `ax^2 + bx + c= 0 ` is the expression inside the square root of a quadratic formula.

Hence,

`discriminant = b^2 - 4ac`

In `6p^2-2p -3=0` , the values of a, b and c are 6, -2 and -3, respectively.

Substituting...

## See

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

The discriminant of an equation in the form `ax^2 + bx + c= 0 ` is the expression inside the square root of a quadratic formula.

Hence,

`discriminant = b^2 - 4ac`

In `6p^2-2p -3=0` , the values of a, b and c are 6, -2 and -3, respectively.

Substituting these values to the formula yields,

`discriminant = (-2)^2 - 4*6*(-3)=4+72=76`

**Hence, the discriminant of `6p^2-2p -3=0` is 76.**